Many-body tunneling dynamics of Bose-Einstein condensates and vortex states in two spatial dimensions - Beinke, Raphael; Klaiman, Shachar; Cederbaum, Lorenz S.; Streltsov, Alexej Iwanowitsch; Alon, Ofir E. (Physical review. A, Atomic, molecular, and optical physics, 2015)
In this work, we study the out-of-equilibrium many-body tunneling dynamics of a Bose-Einstein condensate in a two-dimensional radial double well. We investigate the impact of interparticle repulsion and compare the influence of angular momentum on the many-body tunneling dynamics. Accurate many-body dynamics are obtained by solving the full many-body Schrödinger equation. We demonstrate that macroscopic vortex states of definite total angular momentum indeed tunnel and that, even in the regime of weak repulsions, a many-body treatment is necessary to capture the correct tunneling dynamics. As a general rule, many-body effects set in at weaker interactions when the tunneling system carries angular momentum.
Gesehen am 19.05.2020